Pengaruh Implementasi Hubungan Karyawan Dan Motivasi Kerja Terhadap Kinerja Karyawan Di Balai Besar Standardisasi Dan Pelayanan Jasa Industri Bahan Dan Barang Teknik Bandung - Putri, Thessa Anenda; Luterlean, Bachrudin Saleh (eProceedings of Management, 2024)
The relationship between employees, work motivation, and employee performance is usually a major focus in variousorganizational contexts. The purpose of this study is to study how the interaction between employees and workmotivation affects the performance of employees at the Bandung Centre for Standardization of Engineering Materialsand Goods, individually and overall. This study used a quantitative approach using both descriptive and causalapproaches. Secondary data are obtained from literature studies and other relevant sources. In the case of theBandung Technical Materials and Goods Standardization centre, primary data was collected through directinterviews, observations, and questionnaires. A total sampling of 128 employees was used, and the data was analysedusing multiple linear regression. Research at the Bandung centre for Standardization of Materials and EngineeringGoods shows that the implementation of employee relationships, work motivation, and employee performance are inthe good category. The results indicate employee relationships and work motivation have a positive and significanteffect on employee performance.Keywords-employee relationship implementation, work motives, employee performance